PENGARUH GAYA KEPEMIMPINAN, DISIPLIN KERJA, DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN DI PT. MITRA SEHATI SEKATA YOGYAKARTA - Erwan Sutrisno; Edi Setiawan (Sekolah Tinggi Teknologi Kedirgantaraan, 2023)
The study aims to examine the influence of Leadership Style, Work Discipline, and Work Environment on Employee Performance at PT. Mitra Sehati Sekata Yogyakarta. This type of research uses quantitative research methods. The sample in this study is all employees of PT. Mitra Sehati Sekata Yogyakarta, which has 71 employees. The analytical tests used in this study were the research instrument test, the classical assumption test, the linear multiple regression analysis test, the hypothesis t and F test, the correlation coefficient of R test, and the coefficient determination of R square test. The research result shows that Leadership Style influenced significantly to the Employee Performance. Work Discipline influenced significantly to the Employee Performance. Work Environment influenced significantly to the Employee Performance. Leadership Style, Work Discipline, and Work Environment simultaneously has influence significantly to Employee Performance with a significance F value for 0,000. Keywords: Employee Performance; Leadership Style; Work Discipline; Work Environment